Subjective Age and Cystatin C Among Older Adults. (16th October 2017) - Stephan, Yannick; Sutin, Angelina R; Terracciano, Antonio
Abstract: Objective: Cystatin C (CysC) is a marker of kidney function that is relevant for the health and cognition of older adults. Little is known about the link between psychological factors and CysC. Therefore, the present study examined whether subjective age is related to CysC level and changes in CysC over time. Method: Participants were 5, 066 individuals drawn from the Health and Retirement Study aged from 50 to 107 years (60% women, mean age = 69.36 years, SD = 9.54). They provided data on subjective age, demographic covariates, and CysC at baseline. CysC was assessed again 4 years later. Results: Analysis revealed that an older subjective age was related to higher level of CysC at baseline and to an increase in CysC over 4 years, controlling for demographic factors. An older subjective age was also related to higher risk of exceeding the clinical threshold of CysC at baseline and 4 years later. Additional analysis revealed that disease burden, depressive symptoms, physical inactivity, and BMI partly mediated these associations. Conclusion: The present study provides new evidence on the role of subjective age as a psychological factor associated with individuals' risk of kidney dysfunction, an association beyond chronological age.